Pengaruh Sistem e-Billing pajak dan e-Filling Terhadap Tingkat Kepatuhan Wajib Pajak Badan - Melatnebar, Benyamin (Universitas 17 Agustus 1945 Jakarta, 2018)
Indonesia government generally and Taxation General Directorate especially, should be proud because they develop the tax instrument canal such as; Tax e-Billing and also e-Filling. It easier the taxpayer especially for corporate taxpayer to report their yearly and monthly tax report. So, the obligation of taxpayer to report their tax report, meet the compliance due to Taxation General Directorate. This becoming the best way to increase Indonesia government income significantly. The author of this article conclude that these two tax instrument canal such as tax e-Billing and also e-Filling give the best way to influence the company being comply what the Tax Directorate asked.Since self assessment systems is applicable for taxpayer and education level of taxpayer also influenced the implementation of tax e-Billing and e-Filling, made the corporate taxpayer to comply their tax obligation to Indonesia government. The procedure easiest the corporate taxpayer to fulfill their tax liability. Key words: Taxpayer, Tax e-Billing, e-Filling, Taxation General Directorate, compliance, self assessment system, tax liability